Long-term unemployment, technical progress and capital mobility in an open growth-matching model - Angela Birk (Hamburg Institute of International Economics (HWWA), 2002)
How does technical progress affect long-term unemployment in a small open economy? This relationship is evaluated in an open neoclassical growth model that is extended by a Pissarides-style labor market matching approach. In the general equilibrium model, the labor market of the three factor growth model is characterized by immobile heterogeneous jobless workers. International capital mobility represents the efficient intertemporal allocation of world resources. Depending on a parametric growth condition, an increase in technical progress implies a favorable capitalization effect respectively an unfavorable Schumpeterian creative destruction effect. Secondary effects in form of a stigmatization and a human capital depreciation effect are generated and influence the unemployment duration and the fraction of long-term unemployment negatively. Additionally, the model shows that even in the steady state a constant current account deficit for a net debtor is sustained that rises even more as productivity growth increases. – – Wie beeinflusst der technische Fortschritt die Langzeitarbeitslosigkeit in einer kleinen geöffneten Ökonomie? Diese Beziehung wird in einem geöffneten neoklassischen Wachstumsmodell evaluiert, das um einen Arbeitsmarkt nach der Formulierung des Matching-Ansatz von Pissarides erweitert wird. In dem allgemeinen Gleichgewichtsmodell ist der Arbeitsmarkt des Drei-Faktor-Wachstumsmodell durch immobile, heterogene Arbeitslose charakterisiert. Internationale Kapitalmobilität repräsentiert die effiziente intertemporale Allokation von weltweiten Ressourcen. Abhängig von einer spezifischen Wachstumsbedingung impliziert eine Erhöhung des technischen Fortschritts einen positiven Kapitalisierungseffekt bzw. einen negativen Schumpeterschen kreativen Zerstörungseffekt. Sekundäre Effekte in Form eines Stigmatisierungs- und eines Humankapital- Abwertungs-Effekt werden generiert und beeinflussen sowohl die Dauer der Arbeitslosigkeit als auch die Langzeitarbeitslosigkeit negativ. In dem Modell wird zusätzlich gezeigt, dass erstaunlicher Weise im Steady State ein konstantes Leistungsbilanzdefizit für ein Netto-Schuldner Land aufrecht erhalten wird, das bei steigendem technischen Fortschritt größer wird.
Keywords: E24; F41; O41; 330; long-term unemployment; technical progress; capital mobility; growth; Langzeitarbeitslosigkeit; Arbeitsmarkttheorie; Theorie der Arbeitslosigkeit; Matching; Technischer Fortschritt; Internationale Kapitalmobilität; Kleines-offenes-Land; Wachstumstheorie; Beschäftigungseffekt; Theorie